Penerapan Sistem Informasi Perpustakaan Berbasis Web di Desa Tuyuhan Dukuh Muragan Rembang - Fajar Sodiq; Damayanti, Damayanti; Selvida Widi Audria; Reza Maulana Saputra (Yayasan Literasi Sains Indonesia, 2024)
In this community service, the aim is to increase the reading interest of students and Tuyuhan village residents in particular, as well as digitizing all library administration patterns which previously still used manual methods written in books. By using a direct approach to partners (interviews) about what the information system needs are. So that in creating an information system there is a foundation for the needs in the menu that will appear in the information system. When the training activities were carried out, the enthusiasm of the managers and officers was quite good so that the library information system training received a fairly good response. This library information system training has never been received before so that participants have new experience in implementing digital administration using a library information system. To support participants' understanding in the final session of the training, an evaluation was given so that participants truly understood the essence of the training. To resolve participants' problems after evaluating the library information system, additional sessions were provided for assistance assisted by student members from YPPI Rembang University. Students are given the task of helping participants after completing the training and handing over the library information system to the Gama Bina Karya library management.